3D digital study of the historic ship-model “ARIS” of Admiral Miaoulis from the 19th century – VHSS Project; Preliminary Report - Harlaftis, Gelina; Vosinakis, Spyros; Nikolakopoulou, Vasiliki; Politopoulos, Nikolaos; Bintsi, Eleni; Tourtas, Alexandros; Damianidis, Kostas; Tzavaras, Georgios (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The study of the ship-model of “Aris” of Admiral Miaoulis (Andreas Vokos) (1769–1835) was undertaken in the frame work of the VHSS project. The model was recorded and reconstructed by photogrammetry, laser scanning and conventional measurements. Although it was donated in 1933 (Benaki Museum/Athens), it is considered to have been built during the lifetime of the Admiral. It has a length of 64 cm and it is planked on the starboard side and unplanked on the port side. We propose that the model was built by a shipwright in a scale 1/75. The brig “Aris” was built around 1813 in the shipyards of the island of Hydra and became the flagship of the Greek fleet during the War of Independence.